Urban Development and the Poor. (December 2014) - Hashim, S.R.
With economic growth and increasing diversification of economic activities away from primary sector, urbanisation has been constantly expanding all over the world. This process in India has been slow, and India today is one of the least urbanised countries of the world. Dependence on agriculture for work is still very high. A typical worker in India, by tradition and habit, is a reluctant migrant. He/she moves to the city only when city needs him/her. GDP growth in India has not contributed much to growth in job opportunities. India jumped from primary to tertiary sector bypassing the growth of manufacturing against the historical experience of developed countries and of China in recent years. This has to change. With reasonable assumption about economic growth with industrial development it would be reasonable to expect an urban population of nearly 50 per cent by 2031. Across the states, India has varied experience in urbanisation, ranging from 10 per cent to nearly 60 per cent and above. Levels of urbanisation and levels of economic development of states are highly correlated. More urbanised states also show better urban governance. Situation in small towns in less developed states in most cases is quite dehumanising. Urban planning has been almost non-existent. When asked to propose city development plans (CDPs) for assistance under the Jawaharlal Nehru National Urban Renewal Mission (JnNURM), most of bigger cities propose to move from secondary sector to tertiary sector without showing much concern for implications of such movement for the urban poor. Poverty is not comparable over time with a fixed measuring rod. The urban poor suffer from a large number of vulnerabilities: residential, occupational and social. Residential vulnerabilities are the most acute. Urban poor need to be identified on the basis of these vulnerabilities. If this is done, the magnitude of urban poverty may turn out to be much larger than what the official estimates indicate.